The Early Upper Paleolithic of Croatia - Karavanić, Ivor (1998)
Early Upper Paleolithic industries from Vindija and Velika Pećina caves in Hrvatsko Zagorje (North-Western Croatia) are discussed together with their chronological and paleontological framework. The earliest Upper Paleolithic of these sites follows Mousterian occupations and differs significantly from the Western European Aurignacian. It is also different from the Central European Aurignacian, but is quite similar to industries from Slovenian Alpine sites of Potočka Zijalka and Mokriška jama.